Primary dealer systems in the European Union - Jenny Preunkert (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2020)
States require money to function and therefore every government has to continuously raise new funds. On the financial markets, governments cannot be sure that auctions of their debt will be sufficiently attractive to financial investors, which is why governments usually enter into cooperative agreements with selected banks. The best known and most widespread form of cooperation is the primary dealer system. Primary dealers are banks that agree to participate regularly in government debt auctions and to act as formalized market makers on government debt markets. The article analyzes European primary dealer systems and asks why banks are willing to participate in these systems. I will show that both domestic and foreign banks use their status as primary dealers to build long-term relationships with one or more European governments and to gain an advantage on the global stage. In Bourdieu's terms, primary dealer banks use their financial capital to accumulate social and symbolic capital.
Keywords: 330; Europe; financial markets; government debt market; hierarchy; international competition; sociology